Reclassificação do risco cardiovascular estimado pelo Escore de Framingham utilizando o conceito dos critérios agravantes - Nascimento, Thiago Augusto Silva (2009)
Coronary heart disease (CHD) is one of the main causes of death in the world and Framingham Risk Score (FRS) is the most used tool to assess the risk of CHD in asymptomatic patients. However, it underestimates the cardiovascular (CDV) risk in some individuals. To address this problem, Brazilian Society of Cardiology proposes further risk stratification tests, using emerging risk factors - known as aggravating risk factors - that, when present, reclassify the risk category to a higher one than that initially estimated by the FRS. One does not know which of these aggravating risk factors have more influence in this reclassification, nor the frequency of each CDV risk category after their use and its financial cost. In an observational, descriptive study, 66 patients (54,8 ± 13,9 years, 33 men and 33 women) from a private clinic at Aracaju, Sergipe, had been evaluated during their routine medical exams. Forty three (65.2%) patients were at low-risk category and 23 (34.8%) at the intermediate risk. All of them had been submitted to the screening of the following aggravating risk factors: familiar history of premature CHD (FHCHD), metabolic syndrome (MS), left ventricular hypertrophy (LVH), high sensitivity C reactive protein (CPRus), chronic renal failure (CHF) and subclinical carotid atherosclerosis (SCA). Fifty seven individuals (86.4%) had presented some aggravating risk factors, and MS was the most frequent (68.2%), followed by LVH (34.9%), high CPRus (27.3%), SCA (25.8%), FHCHD (16.7%) and CHF (15.2%). After the reclassification, eight patients (12.1%) were of low risk, 36 (54.6%) of intermediate risk and 22 (33.3%) of high CDV risk. The combined diagnosis of MS and FHCHD was the less expensive strategy of reclassification, changing the risk of 48 patients (72.2%) with a cost of US$ 4,60 per each reclassified individual. The most expensive (US$ 327,52 each patient) was the isolated diagnostic of SCA, that changed the risk of only 17 patients (25.8%). Therefore, FRS underestimated CDV risk in the majority of the evaluated patients, because the frequency of risk enhancers was high, especially metabolic syndrome. Combined screening of the aggravating risk factors seems to be the better strategy. However, this screening must be individualized so as not to have unnecessary expenses.